2023
DOI: 10.1002/glia.24337
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Kir4.1 channels regulate locomotion by orchestrating neuronal rhythmicity in the spinal network

Abstract: Neuronal rhythmogenesis in the spinal cord is correlated with variations in extracellular K + levels ([K + ] e ). Astrocytes play important role in [K + ] e homeostasis and compute neuronal information. Yet it is unclear how neuronal oscillations are regulated by astrocytic K + homeostasis. Here we identify the astrocytic inward-rectifying K + channel Kir4.1 (a.k.a. Kcnj10) as a key molecular player for neuronal rhythmicity in the spinal central pattern generator (CPG). By combining two-photon calcium imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…The broad range of effects on neuronal rhythmicity induced by infrared stimulation may stem from the varied subtypes of oscillatory neurons within the spinal locomotor CPG 45 . The oscillatory behavior of spinal interneurons is heavily influenced by glutamatergic synaptic transmission 65,66 , which is engaged by repetitive infrared pulses. Further investigation into these observations is warranted to elucidate the extent and manner in which each neuronal subtype within the locomotor CPG is modulated by infrared stimulation.…”
Section: /17mentioning
confidence: 99%
“…The broad range of effects on neuronal rhythmicity induced by infrared stimulation may stem from the varied subtypes of oscillatory neurons within the spinal locomotor CPG 45 . The oscillatory behavior of spinal interneurons is heavily influenced by glutamatergic synaptic transmission 65,66 , which is engaged by repetitive infrared pulses. Further investigation into these observations is warranted to elucidate the extent and manner in which each neuronal subtype within the locomotor CPG is modulated by infrared stimulation.…”
Section: /17mentioning
confidence: 99%
“…Astrocytic K + signalling is involved in K + and glutamate homeostasis ( Djukic et al, 2007 ; Kucheryavykh et al, 2007 ), regulation of neuronal oscillations ( Bellot-Saez et al, 2018 ), neural rhythms, hyperexcitability, synaptic plasticity, and locomotor behaviour ( Bellot-Saez et al, 2017 ; Kelley et al, 2018 ; Barbay et al, 2023 ). Retrieval of K + from the extracellular milieu is essential to prevent pathological accumulation of K + in the extracellular space ( Ransom, 1996 ; Bellot-Saez et al, 2017 ; Bellot-Saez et al, 2021 ), if not can result in depolarization of nearby neurons that affects their excitability profile ( Do-Ha et al, 2018 ).…”
Section: Astrocytic Modulation Of Neuronal Signalling At the Molecula...mentioning
confidence: 99%
“…Additionally, Kelley et al demonstrated that astrocytic K ir 4.1 channels in the spinal cord are essential to induce and maintain muscle peak strength by fast alpha motor neurons, indicating that astrocytes impact the electrophysiological properties of alpha motor neurons and overall locomotor activity ( Kelley et al, 2018 ). Moreover, dysfunctional astrocytic K ir 4.1 channels in the spinal central pattern generator led to perturbed locomotor patterns and neuronal rhythmogenesis ( Barbay et al, 2023 ) and it has been suggested that elevated cortical [K + ] o can impact sensory and motor processing by altering neural activity, pointing to an astrocytic role in steering such behaviours ( Rasmussen et al, 2019 ). Another potential mechanism in which astrocytes modulate neuronal oscillations has been suggested by ( Shibasaki et al, 2014 ), who showed that transient receptor potential vanilloid 4 positive (TRPV+) astrocytes can release gliotransmitters, namely, glutamate and ATP, which regulates the excitability of neurons.…”
Section: Astrocytic Regulation Of Neuronal Signals At the Network And...mentioning
confidence: 99%
“…Both DA and NA contribute to the regulation of motor behaviours and to the modulation of nociception (Fleetwood-Walker et al, 1988;Koblinger et al, 2018;Piña-Leyva et al, 2022). Studies have also revealed that spinal astrocytes play a significant role in motor function and nociception by modulating the strength of synaptic transmission (Acton et al, 2018;Acton & Miles, 2015;Barbay et al, 2023;Broadhead & Miles, 2020;Carlsen et al, 2021;Carlsen & Perrier, 2014;Christensen et al, 2013Christensen et al, , 2018Kohro et al, 2020). Nevertheless, the potential interaction between catecholamines and spinal astrocytes has remained largely unexplored.…”
mentioning
confidence: 99%